The battle for the crystal castle ebook - Stilton, Geronimo (Geronimo Stilton and the Kingdom of Fantasy, 2020)
Fairies, dragons, wizards, and more await Geronimo on every magical Kingdom of Fantasy adventure! The Kingdom of Fantasy is in danger again! Geronimo must help keep a famous evil pirate from stealing the dragon egg of fire.